Survey on the current status of international students educational management in China - Shuai Zhu; Juejin Wang; Ying Han; Jun Du (BMC Medical Education)
Abstract Background China has become a new hot spot for foreign students in recent years. The reform of educational management is crucial to improving the quality of teaching and supporting student learning; however, there is a lack of comprehensive data documenting the current state of management in medical programs for foreign students in China. Methods This study conducted a survey among international students enrolled on medical and surgical bachelor’s degree programs (MBBS) from Nanjing medical university in China. A total of 67 valid questionnaires were collected in this study, including 30 international and 37 Chinese sophomores. The questionnaires focused on the teaching quality, operation system, as well as the attitude to campus life and communication modes of those students. Results The international student group’s mean satisfaction with teaching quality was 2.833 ± 0.348 on a five-point scale, much lower than the native students’ mean score of 3.783 ± 0.417 (p < 0.05). Interestingly, although the impact of the international students’ attitude toward course attraction was similar to that recorded for the Chinese students, they were more unsatisfied with the teacher’s level, the delays in understand what the instructor teaches in class, the failure of accept the teacher’s teaching methods, and the insufficient teaching materials that meet students’ needs. Similarly, the international students expressed less satisfaction than the Chinese students with operation system for education (2.700 ± 0.337 vs. 3.388 ± 0.392, p < 0.05). We also noticed that the international students were shown less adapt to study and life in university than their native counterparts (3.833 ± 1.256 vs. 4.378 ± 0.689, p < 0.05). For international students, the main reasons for this could be that there was substantially lower communication with Chinese teachers and take less part in cultural activities. Conclusion Although the number of international students studying in China were increasing rapidly, international students are less satisfied with medical education management than Chinese students. This study is a microcosm of the current situation of medical education for the international students in China, hoping to improve the quality of their medical education.